ROTUND VERSUS SKINNY OROGENS: WELL-NOURISHED OR MALNOURISHED GOLD? - Goldfarb R.J.; Groves D.I.; Gardoll S. (My University, 2001)
Orogenic gold vein deposits require a particular conjunction of processes to form and be preserved, and their global distribution can be related to broad-scale, evolving tectonic processes throughout Earth history. A heterogeneous distribution of formation ages for these mineral deposits is marked by two major Precambrian peaks (2800 2555 Ma and 2100 1800 Ma), a singular lack of deposits for 1200 m.y. (1800 600 Ma), and relatively continuous formation since then (after 600 Ma). The older parts of the distribution relate to major episodes of continental growth, perhaps controlled by plume-influenced mantle overturn events, in the hotter early Earth (ca. 1800 Ma or earlier). This worldwide process allowed preservation of gold deposits in cratons, roughly equidimensional, large masses of buoyant continental crust. Evolution to a less episodic, more continuous, modern-style plate tectonic regime led to the accretion of volcano-sedimentary complexes as progressively younger linear orogenic belts surrounding the margins of the more buoyant cratons. The susceptibility of these linear belts to uplift and erosion can explain the overall lack of orogenic gold deposits at 1800 600 Ma, their exposure in 600 50 Ma orogens, the increasing importance of placer deposits back through the Phanerozoic since ca. 100 Ma, and the absence of gold deposits in orogenic belts younger than ca. 50 Ma.
Keywords: Precambrian; Precambrian; Докембрий